Al Wakalah and Customers’ Preferences toward It: A Case Study of Two Takaful Companies in Malaysia - Annuar, Hairul Azlan (Association of Muslim Social Scientists, 2005)
The agency system has been the main distribution channel for insurers. However, Syarikat Takaful Malaysia Berhad (STMB) does not implement it, while Takaful Nasional Sendirian Berhad (TNSB) does. This has a lot to do with juristic opinions (ikhtilaf)on whether a takaful company (mudarib) can use part of the participants’capital (rabb al-mal) to pay for management expenses.An exploratory survey was undertaken to ascertain the respondents’perception on the importance of agents. My study showed that customers prefer the agency system (al-wakalah) and that this system can generate greater benefits (manfa`at) to both parties.